Investigating urban transport mode choice, travel time, and travel cost the case of work-trips using EDSA - Garcia, Glenn Luigi P.; Diaz, Crispin Emmanuel D. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2025)
In the past decade, the mobility landscape in Metropolitan Manila has seen significant changes against the backdrop of urbanization. Ambitious transport modernization efforts, coupled with aggressive infrastructure expansion, were pursued to continuously facilitate economic growth within the region. However, movement of people is still undermined by traffic congestion, while public transport is still seen as the inferior trip mode due to user dissatisfaction, primarily on travel time and cost. In response, the Philippine Government has included the improvement of the EDSA Busway as an instrument to promote public transport usage by expanding and extending its reach across Metro Manila, to which this study aims to supplement.

Through a sequential filtering process, the actual sensitivity of working individuals to segments of travel time and travel cost was identified by distinguishing trip mode options according to the level of these attributes. This was done using the Random Forest model to classify the subject respondents according to their revealed mode choice, such as public transport, private car, or private motorcycle. Upon interpretation of the results through Accumulated Local Effect Plots, it was recognized that working individuals put most importance on managing their waiting time. Moreover, the relative importance of the accounted segments of travel time indicates that they perceive a diminishing uncertainty in securing a seat in their chosen trip mode as they travel towards their destination. Meanwhile, total trip monetary cost mostly remains the second most important trip mode attribute, reflecting the inherent elasticity of demand for mobility in Metro Manila.

Private motorcycles emerged as the leading trip mode option for these working individuals when minimizing their travel time while spending at a relatively lower cost. On the other hand, public transport was found to be the most common choice for relatively shorter ranges of travel. However, relatively higher earning individuals were found to gravitate to private cars even for travel activities with a total in-vehicle travel time of less than twenty minutes.

Hence, improving the EDSA Busway system can capitalize on these tendencies of working individuals related to their choice of trip mode in order to encourage public transport usage in Metro Manila. Overall, an integrative approach to public transport planning is necessary to minimize travel time and cost by matching the level of supply to the level of demand in the context of built environment constraints, especially road capacity.

Situating transit facilities, such as terminals and stations, near common places of origin while maintaining their users' waiting and transfer time to within one minute is recommended so that the system would be comparable to the superior attributes of private means of transport. Adding detours from the shortest path while administering a transfer-agnostic fare structure with due consideration of seat turnover is also recommended to increase ridership, maximize utilization of fleet seating capacity, and achieve cost competitiveness with other trip mode options.
Thesis
Keywords: Urban transportation -- Philippines .; Commuting -- Philippines .; Choice of transportation -- Philippines